Manufacturing and Characterization of 3D Miniature Polymer Lattice Structures Using Fused Filament Fabrication - Rafael Guerra Silva (Polymers, 2021)
The potential of additive manufacturing to produce architected lattice structures is remarkable, but restrictions imposed by manufacturing processes lead to practical limits on the form and dimension of structures that can be produced. In the present work, the capabilities of fused filament fabrication (FFF) to produce miniature lattices were explored, as they represent an inexpensive option for the production of polymer custom-made lattice structures. First, fused filament fabrication design guidelines were tested to assess their validity for miniature unit cells and lattice structures. The predictions were contrasted with the results of printing tests, showing some discrepancies between expected outcomes and resulting printed structures. It was possible to print functional 3D miniature open cell polymer lattice structures without support, even when some FFF guidelines were infringed, i.e., recommended minimum strut thickness and maximum overhang angle. Hence, a broad range of lattice structures with complex topologies are possible, beyond the cubic-type cell arrangements. Nevertheless, there are hard limits in 3D printing of miniature lattice structures. Strut thickness, length and orientation were identified as critical parameters in miniature lattice structures. Printed lattices that did not fully comply with FFF guidelines were capable of bearing compressive loads, even if surface quality and accuracy issues could not be fully resolved. Nevertheless, 3D printed FFF lattice structures could represent an improvement compared to other additive manufacturing processes, as they offer good control of cell geometry, and does not require additional post-processing.